Visual Processing Deficits in Schizophrenia. - Aworunse, Feyi (Optometry & Visual Performance)
Schizophrenia has been shown to be associated with deficits in higher-order processing of visual information. This literature review explores evidence supporting deficits and dysfunction in areas of pattern recognition, visual scanning, motion processing, and visual attention resulting in altered perception of visual stimuli and reality in patients with schizophrenia. The goal is to help clinicians better understand the disorder for therapeutic and management considerations. Evidence supporting potential pathophysiological processes in the retina and central nervous system offer potential diagnostic value for optometrists, as well as potential benefit from visual rehabilitation for patients with schizophrenia.